2023
DOI: 10.1136/gpsych-2023-101282
|View full text |Cite
|
Sign up to set email alerts
|

Mental stress, atheroma, myocardial ischaemia and injury: the link is inflammation

Hean Teik Ong,
Jinghong Chen

Abstract: Increasing observational and experimental trial data have shown that mental stress can lead to an increase in adverse clinical cardiovascular events. Mental stress affects the heart by inducing ischaemia and precipitating myocardial infarction (MI) or direct myocardial injury. Mental stress leads to systemic inflammation. Inflammation is known to cause rapid atheromatous plaque progression, instability and thrombosis—the classic type 1 MI. Inflammation can also lead to type 2 MI or myocarditis and injury. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Additional data suggest that inflammation can link mental stress to CVD. 6 Previous studies have indicated that an inflammation process fuelled by irregularities in the immune system could potentially explain the connection between CAD and depression. This is evident in the heightened concentrations of interleukin-6, C reactive protein (CRP), fibrinogen and triglycerides.…”
Section: Introductionmentioning
confidence: 99%
“…Additional data suggest that inflammation can link mental stress to CVD. 6 Previous studies have indicated that an inflammation process fuelled by irregularities in the immune system could potentially explain the connection between CAD and depression. This is evident in the heightened concentrations of interleukin-6, C reactive protein (CRP), fibrinogen and triglycerides.…”
Section: Introductionmentioning
confidence: 99%